The Effect of Teaching Formulaic Sequences through Spaced and Non-spaced Retrievals on Iranian EFL Learners' Oral Fluency - Sasan Baleghizadeh; Samaneh Shafeie (Journal of English Language Teaching and Learning, 2019)
Formulaic sequences (FSs) are among the most commonly discussed and well-documented effective factors in oral fluency both in L1 and L2. The present study aims to investigate the effect of teaching a set of 140 FSs on Iranian EFL learners' oral fluency. The relationship between the use of FSs and different measures of oral fluency is also studied empirically. Forty-eight intermediate EFL learners took part in the study. The participants were randomly assigned into two experimental groups and one control group. One of the experimental groups was taught the FSs with spaced retrievals. The other experimental group was also taught the FSs but with non-spaced retrievals. The control group was taught no FSs. The posttest was conducted one week after the treatment. Multivariate analysis of variance (MANOVA) and other statistical procedures were used for analyzing the data. The results indicated that spaced productive retrieval of the FSs after their explicit and holistic teaching, helped the learners to have longer mean length of runs. The present findings have important implications for solving students' problems in speaking the second language. Therefore, the significance of spaced retrieval of FSs in language teaching and learning should not be neglected.